Evaluate lands at some villages located in Syrian Akar plain in Tartous - Mohamed, Safwan; Habib, Hassan; Al - Misbir, Waseem (Arab Journal for Sciences and Research Publishing, 2015)
The objective of this study was to evaluate the suitability of the land at three villages located in Syrian Akar plain in Tartous for current use by comparing crop requirements and soil properties. The FAO framework for Land evaluation was used to evaluate the suitability of land according to Sys 1991, for current use crops (wheat –citrus) according to Simple limitation method and Limiting method regarding number and intensity of limitation. The evaluation showed that there is a sever limitation on citrus, while there is no limitation on wheat.